Cognitive reflection and 2D:4D: Evidence from a large population sample - Levent Neyse; Frank M. Fossen; Magnus Johannesson; Anna Dreber (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Bosch-Domènech et al. (2014) reported a negative association between 2D:4D, a suggested marker of prenatal testosterone exposure, and the Cognitive Reflection Test (CRT) in a sample of 623 university students. In this pre-registered study, we test whether we can replicate their findings in a general population sample of over 2,500 individuals from Germany. We find no statistically significant association between 2D:4D and the CRT in any of our primary hypothesis tests, or in any of our pre-registered exploratory analyses and robustness tests. The evidence is strong (based on the 99.5% confidence intervals in all three primary hypotheses tests) against effect sizes in the hypothesized direction larger than 0.075 CRT units (0.073 of the CRT standard deviation) for a one standard deviation change in 2D:4D.
Keywords: D87; D9; 330; Cognitive Reflection Test; 2D:4D; Replication; Prenatal Testosterone; Sex